PENGARUH KEPEMIMPINAN ETIS DAN GOOD CORPORATE GOVERNANCE TERHADAP KINERJA PERUSAHAAN BUMN DI INDONESIA - Mulyadi Mulyadi (Media Riset Akuntansi, Auditing & Informasi, 2021)
The purposed of this study to examined the influence of ethical leadership on the performance of SOEs in Indonesia, either directly or via a variable good corporate governance practices as a mediating variable. This study using both of primary data, ethical leadership variable and secondary data, good corporate governance index and performance of SOEs. SOEs performance are extracted from two type, first the company's health and assessment criteria for performance excellence. Both of these performance measures has been assesed both of by internal assessment and also the SOE and independent parties.This research used data of 63 state-owned enterprises with such criteria. Primary data such as ethical leadership data, obtained from the Vice President, Senior Vice President of 63 SOEs. SOEs data obtained from internal asesment and by independen party. Results of the study revealed that ethical leadership significant effect on organizational performance. Ethical leadership directly positive significant effect on organizational performance, while good corporate governance can not be a mediating variable. This study also proved significant influence ethical leadership positively to good corporate governance. Other findings, good corporate governance positively affects organizational performance. Ethical leadership a more direct impact on organizational performance compared to the indirect influence through the mediating variables of good corporate governance. The findings reveal the higher index of corporate governance and ethical leadership, the higher the performance of the organization.